DETERMINATION OF ENERGY CONSUMPTION STANDARD FOR STATIONARY CONSUMERS ON THE BASIC WORK OF RAILWAYS - Kuznetsov, V. G. (Science and Transport Progress, 2007)
Regressive dependences are offered for determination of electric power consumption norms for stationary users to the basic operation of railways.